Characteristics of Frequency Response Function Obtained from Equation of Ship Roll Motion Including Nonlinear Restoration Term - UENO, Kimihiko; HIDA, Yoshinobu (Journal of Fisheries Engineering, 2019)
To perform the forced roll test using a model ship, it is necessary to accurately estimate the resonance frequency of the roll. If the restoring term of the equation of motion is linear, the frequency response function is a monovalent function. However, assuming that the restoring term is nonlinear, so that it becomes more realistic, the frequency response function becomes a multivalued function. In this study, this problem was overcome using a complete elliptic integral of the first kind.